The little penguin - Wood, A. J., 1960-; Boey, Stephanie (New York : Dutton Children's Books, 2002)
A little penguin is disappointed because he is not like his father, but in time he learns self-acceptance.
K-3
3.7
Keywords: Emperor penguin -- Fiction; Penguins -- Fiction; Animals -- Infancy -- Fiction; Emperor penguin -- Juvenile fiction; Penguins -- Juvenile fiction